Hand, foot, and mouth disease in adults: An enigma among diagnosticians - A case series - Benila Mathew; Sunila Thomas; Vivek Velayudhan; Ranimol Prasanna (Wolters Kluwer Medknow Publications, 2015)
Hand, foot, and mouth disease (HFMD) is a highly contagious enterovirus infection mainly affecting children less than 5 years of age. In a majority of cases, it is caused by coxsackievirus A16 (CVA16), although instances have been described in which A5, A6, A7, A9, A10, B2, B5, or human enterovirus 71 (HEV-71) has been isolated. The disease occurs rarely in adults, and has been reported in immunocompromised patients. It usually has a benign and self-limiting course with an incubation period of 3-10 days. The prodromal symptoms include fever, malaise, and sore throat. This initial phase is usually followed by erythematous macules, papules, and vesicles on palm and soles, lateral and dorsal surfaces of hands and feet, and also the oral cavity. The purpose of this article is to highlight to the general practitioner about the atypical presentation in healthy adults as well. In the present paper, we describe three cases of HFMD in otherwise healthy adults, with complete recovery.